Вы находитесь на странице: 1из 1

:

c' = 0
(cu) = cu
(u + v) = u + v
(u v) = u v
(uv) = uv + uv
(u / v) = (uv uv)/v2
z=g[f(x)]=F(x)
F(x)= (g(f(x)))x=g(y)*f(x)
:
(xn) = nxn-1
(ln x) = 1 / x
(ex) = ex
(cos x) = sin x
(arccos x) = 1 / sqrt(1 x2)
(arcctg x) = 1 / (1 + x2)

(loga x) = 1 / (x ln a)
(ax) = ax ln a
(sin x) = cos x
(arcsin x) = 1 / sqrt(1 x2)
(arctg x) = 1 / (1 + x2)

:
- :
g(x) f(x0) + f(x0)(x-x0)/1! + f(x0)(x-x0)2/2! + +
f(n)(x0)(x-x0)n/n!
g(x) nk=0 f(k)(x0)(xx0)k/k! = Pn(x)
:
f(x) = Pn(x) + Rn(x), Rn(x)
( )
Rn(x) = f(n+1)(x+(x-x0))(x-x0)n+1/(n+1)!
(0<<1)
:
y = f(x0)(x-x0) + f(x0) -
y = (-1/f(x0))(x-x0) + f(x0) -
-:
:
sin x = +-sqrt(1 cos2 x)
cos x = +-sqrt(1 sin2 x)
sin x = +-tg x / sqrt(1 + tg2 x) cos x = +-1 / sqrt(1 + tg2 x)
sin x = +-1 / sqrt(1 + ctg2 x)
cos x = +-ctg x / sqrt(1+ctg2 x)
tg x = +-sin x / sqrt(1 sin2 x)
tg x = +-sqrt(1cos2 x) / cos x

ctg x = +-sqrt(1 sin2 x) / sin x


ctg x = +-cos x / sqrt(1cos2 x)

.
sin(a +- b) = sin a cos b +- cos a sin b
cos(a +- b) = cos a cos b -+ sin a sin b
tg(a +- b) = (tg a +- tg b) / (1 -+ tg a tg b)
ctg(a +- b) = (ctg a ctg b -+ 1) / (ctg b +- ctg a)
:
sin 2a = 2sin a cos a
cos 2a = 1 2sin2 a
tg 2a = 2tg a / (1 tg2 a)

cos 2a = cos2 a sin2 a


cos 2a = 2cos2 a 1
ctg 2a = (ctg2 a 1) / 2ctg a


sin2 a = (1 cos 2a) / 2

cos2 a = (1 + cos 2a) / 2


:
1)
2) ;
3) , ;
4) , ;
5) ;
6) ;
7)
f(x):
1) -;
2)
f(x): ,


:
:
1) - f(x) g(x) [a,b];
2) f(x) g(x) (a,b);
3) g(x)0 (a,b)
c a<c<b , :

[f(b)-f(a)]/[g(b)-g(a)] = f(c)/g(c) -
:
( )
g(x) = x g(x) = 1
[f(b) f(a)] / (b-a) = f(c)
f(b) f(a) = f(c)(b-a)
:
[f(x)dx] = (F(x)+C) = f(x)
d[f(x)dx] = f(x)dx

Af(x)dx = Af(x)dx
[f(x)+g(x)]dx = f(x)dx + g(x)dx
:
u dv = uv v du
:
f(x) dx = f(g(t)) g(t) dt
:
xa dx = xa+1 / (a+1) + c {a-1}

dx / x = ln |x| + c
sin x dx = -cos x + c
cos x dx = sin x + c
tg x dx = -ln |cosx| + c
ctg x dx = ln |sinx| + c
ax dx = ax / ln a + c
dx / [a2 + x2] = (1 / a) arctg(x / a) + c
dx / [a2 x2] = [1 / 2a] ln |(a + x) / (a x)| + c
dx / (a2 x2) = arcsin(x / a) + c
dx / (x2 a2) = ln |x + (x2 a2)| + c
sh x dx = ch x + c
ch x dx = sh x + c
dx / ch2 x = th x + c
dx / sh2 x = cth x + c
dx / cos2 x = tg x + c
dx / sin2 x = -ctg x + c
dx / (1 + x2)=arctg x + c
dx / (1 x2) = arcsin x + c
x dx = x + c